Pengawasan terhadap Izin Mendirikan Bangunan atas Bangunan Gedung di Kota Medan - Paris, Salman; Yanty, Asima (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
This study aims to describe and examine the Supervision of Building Permits (IMB) for Buildings in Medan City. This research uses a descriptive method with a qualitative approach. Data collection was carried out using structured observation, documentation, literature study, and in-depth interviews through purposive and snowball sampling. The results of the study show that the supervision of the Building Permit (IMB) in Medan City has not run optimally. This can be seen from the many buildings that are standing but do not have permits, this can be seen from the results of the building recapitulation that has been written by the Medan City Settlement and Spatial Planning Housing Office in 2021 as many as 448 buildings but 335 of them do not have a valid IMB. This is due to the assumption that people think that managing an IMB is not important and there are still people who do not accept that the building is demolished due to the assumption that people who build a building in an alley feel that it is not necessary to have a Building Permit (IMB) and will not be supervised. In addition, employees who carry out supervision are not adequate, this is due to the lack of Human Resources (HR) owned by the Department of Housing for the Settlement and Spatial Planning of Medan City so that additional human resources are needed so that supervision can be carried out thoroughly in all areas that have been determined.